The Role of the Gut Microbiome on Skeletal Muscle Mass and Physical Function: 2019 Update - Lustgarten, Michael S. (Frontiers in Physiology, 2019)
Within the past year, several studies have reported a positive role for the gut microbiome on the maintenance of skeletal muscle mass, evidence that contrasts previous reports of a negative role for the gut microbiome on the maintenance of whole body lean mass. The purpose of this mini-review is to clarify these seemingly discordant findings, and to review recently published studies that further elucidate the gut-muscle axis.